The Contribution of Tumor Derived Exosomes to Cancer Cachexia - Christopher R. Pitzer; Hector G. Paez; Stephen E. Alway (Cells, 2023)
Cancer cachexia is defined as unintentional weight loss secondary to neoplasia and is associated with poor prognosis and outcomes. Cancer cachexia associated weight loss affects both lean tissue (i.e., skeletal muscle) and adipose tissue. Exosomes are extracellular vesicles that originate from multivesicular bodies that contain intentionally loaded biomolecular cargo. Exosome cargo includes proteins, lipids, mitochondrial components, and nucleic acids. The cargo carried in exosomes is thought to alter cell signaling when it enters into recipient cells. Virtually every cell type secretes exosomes and exosomes are known to be present in nearly every biofluid. Exosomes alter muscle and adipose tissue metabolism and biological processes, including macrophage polarization and apoptosis which contribute to the development of the cachexia phenotype. This has led to an interest in the role of tumor cell derived exosomes and their potential role as biomarkers of cancer cell development as well as their contribution to cachexia and disease progression. In this review, we highlight published findings that have studied the effects of tumor derived exosomes (and extracellular vesicles) and their cargo on the progression of cancer cachexia. We will focus on the direct effects of tumor derived exosomes and their cellular cross talk on skeletal muscle and adipose tissue, the primary sites of weight loss due to cancer cachexia.